Potential for naturally derived therapeutics: the Caribbean as a model – insights from the conference on therapeutics and functional genomics. (October 2014) - Badal, Simone; Collins-Fairclough, Aneisha; Stewart, Cheryl; Smith, Keriayn
Abstract : The 2nd Annual Conference of the Society for Scientific Advancement (SoSA) was convened to integrate three research areas towards the development of therapies that will help to reduce disease burden in the Caribbean. Held in Kingston, the capital city of Jamaica, on November 22, 2013, the meeting assembled experts in the areas of genomics, stem cell research and natural medicine. The speakers represented the University of the West Indies, Mona and St. Augustine campuses, the University of Technology, and faculty from the USA and Africa. Sponsorship of this meeting supports SoSA's goal of stimulating translational research in the Caribbean.